Embedded Metallic Bangle in Vagina - Gupta, T; Gupta, N; Bhatia, P; Gupta, S; Jain, J (Journal of Universal College of Medical Sciences, 2014)
BACKGROUND: Uterovaginal prolapse is a very common morbidity among Indian women. Vaginal pessaries still have role in the management of uterovaginal prolapse. Long forgotten pessaries get incarcerated in the vagina and their removal poses problems. A 65 year old postmenopausal lady presented with pain lower abdomen and thin vaginal discharge. Speculum examination revealed embedded metallic bangle in the vagina. Attempts at removal by gentle traction resulted in pain. Metallic bangle was removed under general anaesthesia and biopsy from the overlying tissue revealed no evidence of malignancy. Vaginal pessary gives symptomatic relief and does not cause any discomfort, women tend to forget it. This case report is unique as here ordinary metallic bangle was used as a vaginal pessary and in spite of long duration it did not cause much discomfort or any serious complication. DOI: http://dx.doi.org/10.3126/jucms.v2i2.11174 Journal of Universal College of Medical Sciences (2014) Vol.2(2): 46-48